STRATEGI PENINGKATAN FASILITAS PANGKALAN PENDARATAN IKAN (PPI) KUALA TUHA, KABUPATEN NAGAN RAYA, ACEH - Cici Dianita; Ernani Lubis; Mustaruddin Mustaruddin (Fakultas Perikanan dan Ilmu Kelautan, 2020)
Activities at the Kuala Tuha Fish Landing Base (PPI) are not optimal because the existing facilities are inadequate, so it needs to be improved again. The purpose of this study was to determine the strategy to improve the PPI Kuala Tuha facility. The research was conducted at PPI Kuala Tuha in February-March 2020 using the case study method. The analysis used is the utilization level and SWOT analysis. The results of the study there are 2 main facilities and 3 functional facilities studied, where all facilities are still inadequate. The results of the calculation of the level of utilization of basic and functional facilities have not been reached optimally. The SWOT analysis produced 8 alternative strategies that could be used to improve basic and functional facilities at PPI Kuala Tuha.